Two Periods of Skarn Mineralization in the Baizhangyan W–Mo Deposit, Southern Anhui Province, Southeast China: Evidence from Zircon U–Pb and Molybdenite Re–Os and Sulfur Isotope Data. Issue 3 (July 2015) - Li, Chunhai; Jiang, Yaohui; Xing, Guangfu; Guo, Kunyi; Li, Chao; Yu, Minggang; Zhao, Peng; Wang, Zheng
Abstract The recently discovered Baizhangyan skarn‐porphyry type W–Mo deposit in southern Anhui Province in SE China occurs near the Middle–Lower Yangtze Valley polymetallic metallogenic belt. The deposit is closely temporally‐spatially associated with the Mesozoic Qingyang granitic complex composed of granodiorite, monzonitic granite, and alkaline granite. Orebodies of the deposit occur as horizons, veins, and lenses within the limestones of Sinian Lantian Formation contacting with buried fine‐grained granite, and diorite dykes. There are two types of W mineralization: major skarn W–Mo mineralization and minor granite‐hosted disseminated Mo mineralization. Among skarn mineralization, mineral assemblages and cross‐cutting relationships within both skarn ores and intrusions reveal two distinct periods of mineralization, i.e. the first W–Au period related to the intrusion of diorite dykes, and the subsequent W–Mo period related to the intrusion of the fine‐grained granite. In this paper, we report new zircon U–Pb and molybdenite Re–Os ages with the aim of constraining the relationships among the monzonitic granite, fine‐grained granite, diorite dykes, and W mineralization. Zircons of the monzonitic granite, the fine‐grained granite, and diorite dykes yield weighted mean U–Pb ages of 129.0 ± 1.2 Ma, 135.34 ± 0.92 Ma and 145.3 ± 1.7 Ma, respectively. Ten molybdenite Re–Os age determinations yield an isochron age of 136.9 ± 4.5 Ma and a weighted mean age of 135.0 ± 1.2 Ma. The molybdenites have δ34S values of 3.6‰–6.6‰ and their Re contents ranging from 7.23 ppm to 15.23 ppm. A second group of two molybdenite samples yield ages of 143.8 ± 2.1 and 146.3 ± 2.0 Ma, containing Re concentrations of 50.5–50.9 ppm, and with δ34S values of 1.6‰–4.8‰. The molybdenites from these two distinct groups of samples contain moderate concentrations of Re (7.23–50.48 ppm), suggesting that metals within the deposit have a mixed crust–mantle provenance. Field observation and new age and isotope data obtained in this study indicate that the first diorite dyke‐related skarn W–Au mineralization took place in the Early Cretaceous peaking at 143.0–146.3 Ma, and was associated with a mixed crust–mantle system. The second fine‐grained granite‐related skarn W–Mo mineralization took place a little later at 135.0–136.9 Ma, and was crust‐dominated. The fine‐grained granite was not formed by fractionation of the Qingyang monzonitic granite. This finding suggests that the first period of skarn W–Au mineralization in the Baizhangyan deposit resulted from interaction between basaltic magmas derived from the upper lithospheric mantle and crustal material at 143.0–146.3 and the subsequent period of W–Mo mineralization derived from the crust at 135.0–136.9 Ma.